(3eNJUQ efGbH YeQ Hf YHO GdYRjRs - (3CSGeI Hf eQO Hf Ydj Hf ebdO Hf efbPs; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3HYO MeO Gddg Ydi LRjd fYeI Effi hbaJ Ydi cJGH efGbH CejQ GdeDefjf YeQ Hf YHO GdYRjR JCdja GdTjN CHj GdaQL Hf GdLhRi aLQOJgG ef GdCSGfjO s
(3BNQgG (B:s
(3hQCjJ QLdG ef hdO YeQ Hf YHO GdYRjR bO Med ai jhe hGMO Ydi eGFI aQS ai SHjd Gddg YR hLd ef Bd jJUOb Ydjg , hgPG BNQ GdcJGH s
(3Vef eLehY s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B553 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B380 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs